2011
DOI: 10.1152/ajplung.00075.2011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of neutrophil apoptosis by PAI-1

Abstract: Increased circulating and tissue levels of plasminogen activator inhibitor 1 (PAI-1) are often present in severe inflammatory states associated with neutrophil activation and accumulation and correlate with poor clinical outcome from many of these conditions. The mechanisms by which PAI-1 contributes to inflammation have not been fully delineated. In the present experiments, we found that addition of PAI-1 to neutrophil cultures diminished the rate of spontaneous and TNF-related apoptosis-inducing ligand-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 51 publications
(53 reference statements)
1
27
0
Order By: Relevance
“…Although we cannot absolutely ascribe this phenotype to elevation in the levels of fibrin and fibrin breakdown products, fluorescence-activated cell sorting (FACS) analysis shows significant increases in lung neutrophil counts, as a function of increasing SARS-CoV dose (data not shown). More recent studies have also shown that Serpine1 inhibits neutrophil apoptosis (53), suggesting that neutrophil recruitment and effector function likely contribute to more severe disease outcomes following SARS-CoV MA15 infection. Similar findings have been reported with highly pathogenic influenza viruses, including H5N1 and 1918 influenza viruses (54).…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot absolutely ascribe this phenotype to elevation in the levels of fibrin and fibrin breakdown products, fluorescence-activated cell sorting (FACS) analysis shows significant increases in lung neutrophil counts, as a function of increasing SARS-CoV dose (data not shown). More recent studies have also shown that Serpine1 inhibits neutrophil apoptosis (53), suggesting that neutrophil recruitment and effector function likely contribute to more severe disease outcomes following SARS-CoV MA15 infection. Similar findings have been reported with highly pathogenic influenza viruses, including H5N1 and 1918 influenza viruses (54).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mouse models reveal that components of the coagulation cascade impact on neutrophil recruitment or their survival. Plasminogen activator inhibitor-1 (PAI-1) enhances neutrophil recruitment after P. aeruginosa infection and exerts antiapoptotic effects on neutrophils via phosphatidylinositol 3-kinase activation in a model of LPSinduced acute lung injury (80,277), increasing neutrophil load in the air spaces. Tissue plasminogen activator (tPA)-deficient mice are protected from lung ischemia-reperfusion injury through inhibition of neutrophil recruitment, which is mediated by the tPA/LDL receptor-related protein/NF-B signaling pathway and reduction in PECAM-1 expression (275).…”
Section: Immune Cells and Inflammatory Signaling Pathways In Alimentioning
confidence: 99%
“…IL-1␤ also promotes the secretion of neutrophil-attracting CXC chemokines, which favor the influx of neutrophils and exacerbate the damage to epithelial cells, and PDGF, which further induces fibrosis. Finally, TGF-␤ and IL-1␤ can increase the expression of plasminogen activator inhibitor 1, which inhibits ECM degradation, promotes recruitment of more inflammatory cells (67), and suppresses the release of antifibrogenic growth factors (30). The initial proinflammatory scenario of inflammasome activation can rapidly progress to a profibrotic one, leading to the chronic and devastating disease.…”
Section: Role Of the Inflammasome In Lung Diseasesmentioning
confidence: 99%